An Unusual Case of Maxillary Sinus Cholesterol Granuloma Showing FDG Uptake on PET/CT. (February 2021) - Umeda, Naoki; Hayama, Masaki; Nakamura, Akiko; Maeda, Yohei; Inohara, Hidenori
Abstract : Abstract: Cholesterol granuloma (CG) occurs primarily in the middle ear and rarely in the paranasal sinus. We report an unusual case of paranasal sinus CG with 18 F-FDG uptake. A 76-year-old man presented with right refractory epistaxis. PET/CT showed FDG uptake in the maxillary sinus. CT findings are typically uncharacteristic, whereas MRI scans are characterized by a high signal on both T1-weighted and T2-weighted images. Nasal endoscopy from the ostium revealed a granulomatous lesion with hemorrhage at the base of the maxillary sinus. After pathological examination by endoscopic sinus surgery, the patient was diagnosed with CG.